Chad : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chad. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The staff report for Chad's 2008 Article IV Consultation presents economic developments and policies. The global economic crisis has affected the budget and reserves through lower oil prices. Chad's limited financial and trade integration has insulated it from the financial crisis and ensuing global recession. Risks include lower demand for exports and weaknesses in the foreign banks that own most of Chad's banking system. Chad is seriously affected by declining oil prices, which will require substantial fiscal adjustment and will lower reserves, albeit not to critical levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet